2022
DOI: 10.1055/s-0042-1759879
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cancer Risk in Patients with Kidney Disease and Venous Thromboembolism: A Population-Based Cohort Study

Abstract: Background Venous thromboembolism (VTE) may be a harbinger of cancer in the general population. Patients with kidney disease have an a priori increased VTE risk. However, it remains unknown how a VTE affects subsequent cancer risk in these patients. Objectives To examine the cancer risk in patients with kidney disease following a VTE. Methods We conducted a nationwide population-based cohort study in Denmark (1996–2017), including all VTE patients with a diagnosis of kidney disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…(versus planned visit), record versus no record of dialysis or kidney transplantation, provoked versus unprovoked VTE, or early versus late (within versus beyond the first 30 days of follow-up) cancer diagnosis; the consistency of the results further strengthens the message of the main analysis (6). On the other hand, several limitations, which are partly unavoidable in this type of research, need to be kept in mind before drawing conclusions:  Firstly, due to the lack of data regarding the severity of kidney disease and that of the VTE episode, it is unclear whether these parameters affected the reported association between nephropathy and cancer, and consequently to what extent they should be considered for planning the intensity of cancer screening and frequency of follow-up.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
See 3 more Smart Citations
“…(versus planned visit), record versus no record of dialysis or kidney transplantation, provoked versus unprovoked VTE, or early versus late (within versus beyond the first 30 days of follow-up) cancer diagnosis; the consistency of the results further strengthens the message of the main analysis (6). On the other hand, several limitations, which are partly unavoidable in this type of research, need to be kept in mind before drawing conclusions:  Firstly, due to the lack of data regarding the severity of kidney disease and that of the VTE episode, it is unclear whether these parameters affected the reported association between nephropathy and cancer, and consequently to what extent they should be considered for planning the intensity of cancer screening and frequency of follow-up.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…A total of 464 patients were diagnosed with cancer, with more than one third of the cases (36%) being confirmed within the first year of follow-up (6). The main finding of this study is undoubtedly the high (5.0%; 95% confidence interval [CI]: 4.3-5.8) one-year absolute risk of any cancer.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…1 Even in this journal there has been much interest in the epidemiology, prognosis, and risk factors for VTE, as well as the pathophysiological mechanisms underlying the propensity to develop this common condition. [2][3][4][5][6][7] Pregnancy is an important risk factor for VTE. Several previous studies reported the incidence of pregnancy-associated VTE (PA-VTE) for Western population.…”
mentioning
confidence: 99%